The wind of rotating B supergiants. I. Domains of slow and fast solution regimes - Venero, Roberto Oscar José (2016)
In the scenario of rotating radiation-driven wind theory for massive stars, three types of stationary hydrodynamic solutions are currently known: the classical (fast) m-CAK solution, the Ω-slow solution that arises for fast rotators, and the so-called δ-slow solution if high values of the δ line-force parameter are allowed independently of the rotation speed. Compared to the fast solution, both "slow solutions" have lower terminal velocities. As the study of the parameter domain for the slow solution is still incomplete, we perform a comprehensive analysis of the distinctive flow regimes for B supergiants that emerge from a fine grid of rotation values, Ω, and various ionization conditions in the wind (δ) parameter. The wind ionization defines two domains: one for fast outflowing winds and the other for slow expanding flows. Both domains are clear-cut by a gap, where a kink/plateau structure of the velocity law could exist for a finite interval of δ. The location and width of the gap depend on Teff and Ω. There is a smooth and continuous transition between the Ω-slow and δ-slow regimes, a single Ω δ-slow regime. We discuss different situations where the slow solutions can be found and the possibility of a switch between fast and slow solutions in B supergiant winds. We compare the theoretical terminal velocity with observations of B and A supergiants and find that the fast regime prevails mostly for early B supergiants while the slow wind regime matches better for A and B mid- and late-type supergiants.